Pengaruh Pijat Bayi Terhadap Perkembangan Neonatus - Miftah - Andini; Riri - Novayelinda; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aims to analize the effect of baby massage for neonates development. This study used quasy experimental design with non-equivalent control group which is devided into experimental and control group. Purposive sampling method was used in this study. Total sample of this study was 30 first born neonates aged 2 weeks. The instrument in this research was observational which is adopted from DDST II. Fifteen neonates as experiment group have been given massage therapy for 2 weeks and will be observed for their development after 4 weeks of aged. The data were analyzed by using Mann Whitney and Wilcoxon test. Mann-Whitney test showed that there was a significant difference of neonates development between experiment and control group with p value 0,000. Wilcoxon test showed the median of development before massage was 5,00 and after massage was 9,00 with p value 0.001. It means that baby massage has an effect on neonates development. Based on this study, it is recommended for using baby massage as one of nursing intervention to increase neonates development. Keywords: baby massage, development